Liking for fat is associated with sociodemographic, psychological, lifestyle and health characteristics. Issue 8 (28th October 2014) - Lampuré, Aurélie; Deglaire, Amélie; Schlich, Pascal; Castetbon, Katia; Péneau, Sandrine; Hercberg, Serge; Méjean, Caroline
<x content-type="archive" xml:space="preserve">Abstract</x> Sensory liking influences dietary behaviour, but little is known about specifically associated individual profiles. The aim of the present study was to investigate the associations between liking for fat-and-salt and fat-and-sweet sensations and sociodemographic, economic, psychological, lifestyle and health characteristics in a large sample. Individual characteristics and liking scores were collected by a questionnaire among 37 181 French adults. Liking scores were constructed using a validated preference questionnaire. Multinomial logistic regression models were used to assess the associations between liking levels and individual characteristics. In both sexes, subjects belonging to low-level occupational categories (OR 1·39, 95 % CI 1·16, 1·67 in men; OR 1·28, 95 % CI 1·16, 1·41 in women), highly uncontrolled eaters (men: OR 2·90, 95 % CI 2·60, 3·23; women: OR 2·73, 95 % CI 2·27, 3·30) and obese subjects (men: OR 1·45, 95 % CI 1·14, 1·84; women: OR 1·47, 95 % CI 1·29, 1·68) were more likely to have a strong liking for the fat-and-sweet sensation, whereas older individuals (men: OR 0·13, 95 % CI 0·10, 0·16; women: OR 0·11, 95 % CI 0·09, 0·14) and highly cognitive restrainers (men: OR 0·52, 95 % CI 0·44, 0·63; women: OR 0·60, 95 % CI 0·55, 0·66) were less likely to have a strong liking. Regarding liking for the fat-and-salt sensation, the same associations were found and specific relationships were also highlighted: current smokers and heavy drinkers were more likely to strongly prefer the fat-and-salt sensation compared with non-smokers and abstainers or irregular alcohol consumers. The relationship between individual characteristics and a liking for fat sensation provides new and original information that may be useful for a better understanding of the associations between sensory liking and individual behaviour.